Exploiting dendritic cells in the development of cancer vaccines. (October 2013) - Bracci, Laura; Capone, Imerio; Moschella, Federica; Proietti, Enrico; Belardelli, Filippo
Due to their central role in priming and modulating the immune response, dendritic cells (DCs) represent an ideal instrument for the design of effective immunotherapeutic strategies for cancer patients. Recent advancement on the knowledge of the numerous DC subtypes, their functions and T-cell polarizing abilities has led to the development of several protocols for the ex vivo differentiation of autologous DCs and their loading with tumor-associated antigens. Moreover, novel strategies for the in vivo targeting of tumor antigens and adjuvants to natural DC subsets have been developed. Despite the large number of clinical studies carried out in cancer patients, a consensus on the optimal treatment modalities has not been reached yet. In this review, we summarize our current knowledge on DC biology and on DC use in clinical trials. Special attention is given to the many open issues regarding DC-based vaccination to sensitize researchers in the field to the compelling need of conducting comparative studies systematically addressing the still unresolved problems.